Ultrastructural localization of DREADDs in monkeys. (19th June 2019) - Galvan, Adriana; Raper, Jessica; Hu, Xing; Paré, Jean‐François; Bonaventura, Jordi; Richie, Christopher T.; Michaelides, Michael; Mueller, Sascha A. L.; Roseboom, Patrick H.; Oler, Jonathan A.; Kalin, Ned H.; Hall, Randy A.; et al.
Abstract: Designer receptors exclusively activated by designer drugs (DREADDs) are extensively used to modulate neuronal activity in rodents, but their use in primates remains limited. An essential need that remains is the demonstration that DREADDs are efficiently expressed on the plasma membrane of primate neurons. To address this issue, electron microscopy immunogold was used to determine the subcellular localization of the AAV vector‐induced DREADDs hM4Di and hM3Dq fused to different tags in various brain areas of rhesus monkeys and mice. When hM4Di was fused to mCherry, the immunogold labelling was mostly confined to the intracellular space, and poorly expressed at the plasma membrane in monkey dendrites. In contrast, the hM4Di‐mCherry labelling was mostly localized to the dendritic plasma membrane in mouse neurons, suggesting species differences in the plasma membrane expression of these exogenous proteins. The lack of hM4Di plasma membrane expression may limit the functional effects of systemic administration of DREADD‐actuators in monkey neurons. Removing the mCherry and fusing of hM4Di with the haemagglutinin (HA) tag resulted in strong neuronal plasma membrane immunogold labelling in both monkeys and mice neurons. Finally, hM3Dq‐mCherry was expressed mostly at the plasma membrane in monkey neurons, indicating that the fusion of mCherry with hM3Dq does not hamper membrane incorporation of this specific DREADD. Our results suggest that the pattern of ultrastructural expression of DREADDs in monkey neurons depends on the DREADD/tag combination. Therefore, a preliminary characterization of plasma membrane expression of specific DREADD/tag combinations is recommended when using chemogenetic approaches in primates. Abstract : We examined the ultrastructural localization of the DREADDs hM4Di and hM3Dq fused to different tags in monkey and mouse neurons. Poor plasma membrane expression was observed with hM4Di‐mCherry in monkeys. In contrast, strong plasma membrane localization was found with HA‐hM4Di in mice and monkeys, hM4Di‐mCherry in mice and hM3Dq‐mCherry in monkeys. Our results suggest that ultrastructural expression of DREADDs depends on the species, and the DREADD/tag combination.